New regional identities in a global world - Antoine Bailly (Global Labor Organization (GLO), 2017)
Regional movements are emerging in Europe, often to promote historical, cultural or economic regions. Are we going to have a new regional Europe with 60 regions instead of 27 nation-states?
Keywords: R11; 330; regions; regional geography; centralisation; federation; confederation